DNA densitometry of colorectal cancer. Issue 11 (November 1993) - Deans, G T; Williamson, K; Hamilton, P; Heatley, M; Arthurs, K; Patterson, C C; Rowlands, B J; Parks, T G; Spence, R A
Abstract : DNA analysis was assessed by densitometry for 281 cases of colorectal adenocarcinoma. Detection of aneuploidy in a single case rose from 65% if one, to 92.5% when three or more sections, were analysed. Although aneuploid tumours had significantly larger nuclear areas than near diploid tumours (p = 0.009), densitometric measurements showed no association with clinicopathological variables. DNA content determined by densitometry was compared with that from flow cytometry on 465 tissue sections from 241 cases. Aneuploidy assessed by flow cytometry was significantly associated with that determined by densitometry (p < 0.01 for all comparisons), ploidy state being similar in 381 sections (82%, kappa = 0.63, p < 0.001), and 187 cases (77.6%, kappa = 0.57, p < 0.001). Univariate survival analysis showed that DNA densitometric variables had no significant association with survival in (a) all cases, (b) cases without lymph node metastases, or (c) cases without distant metastases. Multivariate regression analysis of densitometric and clinicopathological variables identified Dukes's stage, patient age, and tumour differentiation as the combination of variables most closely related to survival. Densitometric measurement of DNA content could not significantly improve on the prognostic model containing these three variables. It is concluded that, although the assessment of DNA content by densitometry is comparable with that of flow cytometry, conventional histological variables remain the best predictors of prognosis in colorectal cancer.